Oral administration of tartrazine (E102) accelerates the incidence and the development of 7,12-dimethylbenz(a) anthracene (DMBA)-induced breast cancer in rats - Stéphane Zingue; Elisabeth Louise Ndjengue Mindang; Florence Charline Awounfack; Abel Yanfou Kalgonbe; Moustapha Mohamet Kada; Dieudonné Njamen; Derek Tantoh Ndinteh (BMC, 2021)
Abstract Background Despite the considerable advances made in the treatment of cancer, it remains a global threat. Tartrazine (E102) is a synthetic dye widely used in food industries; it has recently been shown to induce oxidative stress (a well known risk factor of cancer) in rat tissues. The present work therefore aimed to assess the impact of a regular consumption of tartrazine on the incidence of breast cancer in rats. Methods Forty (40) Wistar rats aged 55 to 60 days were randomly assigned into 5 groups (n = 8) including two groups serving as normal controls and receiving distilled water (NOR) or tartrazine (NOR + TARZ). The three remaining groups were exposed to the carcinogen DMBA (50 mg/kg) and treated for 20 weeks with either distilled water (DMBA), tartrazine 50 mg/kg (DMBA + TARZ) or a natural dye (DMBA + COL). The parameters evaluated were the incidence, morphology and some biomarkers (CA 15-3, estradiol and α-fetoprotein) of breast cancer. The oxidative status and histomorphology of the tumors were also assessed. Results A regular intake of tartrazine led to an early incidence of tumors (100% in rats that received TARZ only vs 80% in rats that received DMBA only), with significantly larger tumors (p < 0.001) (mass = 3500 mg/kg and volume = 4 cm3). The invasive breast carcinoma observed on the histological sections of the animals of the DMBA + TARZ group was more developed than those of the DMBA group. The increase in serum α-fetoprotein (p < 0.05) and CA 15-3 (p < 0.01) levels corroborate the changes observed in tumors. The presence of oxidative activity in animals of the DMBA + TARZ group was confirmed by a significant decrease (p < 0.001) in the activity of antioxidant enzymes (SOD and catalase) as well as the level of GSH and increase in the level of MDA compared to the rats of the DMBA and NOR groups. Conclusion Tartrazine therefore appears to be a promoter of DMBA-induced breast tumorigenesis in rats through its oxidative potential. This work encourages further studies on the mechanisms of action of tartrazine (E102) and its limits of use.